Surface properties and activation energy of superplastically carburized duplex stainless steel - Ahamad, N.W.; Jauhari, I.; Azis, S.A.A.; Aziz, N.H.A. (Elsevier, 2010)
A new surface carburizing technique which combines superplastic phenomenon and carburizing process called superplastic carburizing (SPC) was introduced and compared with conventional carburizing (CC) process. Thermomechanically treated duplex stainless steel (DSS) with a fine grain microstructure that exhibits superplasticity was used as the superplastic material. SPC was carried out at temperatures of 1198-1248 K and a compression rate of 1 x 10(-4) s(-1) for various durations. Metallographic studies revealed that a carbon layer with a uniform, dense and smooth morphology formed on all carburized specimens. The case depth of the carbon layer was between 50.8 and 159.1 mu m. A remarkable increase in surface hardness was observed in the range 389.9-1129.0 HV. Activation energy for SPC was determined as 183.4 kJ mol(-1), which is lower compare to CC process. The results indicate that SPC accelerates the diffusion of carbon atoms into the surface of DSS, thus increasing the thickness of the carburized layer and the surface hardness, at lower activation energy. (C) 2010 Elsevier B.V. All rights reserved.